Advanced exergy analysis and risk estimation of novel NH3-H2O and H2O-LiBr integrated vapor absorption refrigeration system. (15th November 2020) - Jain, Vaibhav; Singhal, Ashu; Sachdeva, Gulshan; Kachhwaha, S.S.
Highlights: Work presents a novel integrated vapor absorption refrigeration system (IVARS). IVARS operates at comparatively low generator temperature with waste heat. CSB and Pareto chart analysis identify the sensitive components of IVARS. 19.8% of the irreversible loss in IVARS is found avoidable. Total annual risk due to toxic fluid is estimated as US$ 996.6/year. Abstract: In present work, thermodynamic potential and risk estimation of NH3 -H2 O and H2 O-LiBr integrated vapor absorption refrigeration system (IVARS) have been reported. The performance of IVARS has also been compared with a conventional vapor absorption refrigeration system (VARS) for the same cooling duty. Comparative results show that the proposed configuration can maintain evaporator temperature of −30 °C with 92.1 °C generator temperature, which is 51.6 °C lower than that required in a conventional VARS. Further, coefficient of structural bonds (CSB) values predict that the solution heat exchanger of NH3 -H2 O subsystem (maximum CSB value 5.28) is the most sensitive heat exchanger; whereas, generator of H2 O-LiBr subsystem (minimum CSB value 0.38) is the most efficient heat exchanger of IVARS, but contrary to this, their involvement in total irreversibility is merely 6.7% and 18.6% respectively. Based on 80/20 principle, Pareto chart suggests the designer to focus on improving the efficiency parameter of generators and absorbers of IVARS due to their significant contribution in total irreversibility rate. Hence, advanced exergy analysis has been performed to overcome this dilemma. Interestingly, 19.8% of the irreversible loss in IVARS is found avoidable and can be eradicated by modifying the efficiency parameters of different components of IVARS and 93.7% of irreversibility rate is due to the selected operating parameters of components itself. Moreover, the total annual risk due to toxic fluid 'ammonia' in NH3 -H2 O absorption subsystem is estimated to be US$ 996.6/year and the condenser of NH3 -H2 O is found to be the major contributor. Present study shows that IVARS has better thermodynamic performance and can be successfully operated using low temperature waste heat with efficient and effective recovery.